Dialogic legacy-making for patients and family caregivers facing end-of-life - Choo, Jue Ying (Nanyang Technological University, 2019)
Legacy interventions have the potential to establish ego-integrity and symbolic immortality, psychosocial needs which become particularly salient nearing end-of-life. To illuminate the processes, components and roles involved in dialogic legacy-making, a new paradigm for legacy interventions, framework analysis was conducted on transcripts from 20 Family Dignity Intervention sessions involving 10 patient-caregiver dyads. Two stages and 12 themes emerged. In the legacy-creation stage, through the positive recollection of shared past and strengths-based co-construction of the self, the patient’s self is captured in his identity, the roles he played and the impact that he had. The caregiver is involved as a witness who, together with the patient, co-constructs the patient’s life narrative and sense of self. In the legacy-transmission stage, the patient’s identity, roles, and impact are respectively preserved in the values imparted to the caregiver, the enduring influence on the family that the patient extends through life-lessons, as well as visions of the future the family is directed to strive towards. The transmission of legacy takes place either actively during the intervention, or passively during the family’s daily lives. The internalization of these components by the caregiver is explicitly signalled to the patient during the intervention. In this way, the caregiver acts as a recipient, receiving the aspects of the patient’s self and carrying them into the future. Dialogic legacy-making establishes multiple and synergistic channels for the formation of ego-integrity and symbolic immortality, above and beyond interventions conducted at the individual level.